Mejorando la efectividad instruccional del texto educativo en ciencias: primeros resultados - Sanjosé López, V.; Solaz Portolés, Joan Josep; Vidal-Abarca Gámez, E. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1993)
In this paper we compile and analyze the textual variables taking part in comprehension and learning processes on scientific texts. Next we propose a new classification which can be applicated to instructional text. This proposal is evaluated in an experiment with different groups of students and several learning tasks. The first results are discussed.